Experimental Characterization of Low-Temperature Inorganic. Phase Change Materials by Differential Scanning Calorimetry - Josh Charles; Xingchao Wang; Carlos E. Romero; Sudhakar Neti (Journal of Advanced Thermal Science Research, 2019)
Recently, phase change materials (PCMs) have received significant attention due to their potential for high-density thermal energy storage. While high-temperature PCMs have received the most focus in the thermal energy storage community, there are potential uses for PCMs with phase transition temperatures close to typical ambient temperatures (15-35°C). For a PCM to be widely used in a large-scale thermal energy storage system, it must meet the cost, safety, and energy density criteria in addition to having an appropriate phase change temperature. Inorganic, hydrated salt PCMs are the most promising, low-temperature PCMs, which can meet all of these criteria. After completing a review of known inorganic PCMs with phase change temperatures in the desired range, six of the more promising PCMs were tested by differential scanning calorimetry (DSC) to determine both their phase change temperatures (Tm) and latent heats of fusion (Hf). The first of these PCMs (potassium fluoride tetrahydrate) was eliminated after successful DSC testing as it became apparent that this PCM had serious health and safety concerns. Two new calcium chloride hexahydrate (CaCl2•6H2O)-based PCMs were also tested: CaCl2•6H2O + potassium nitrate (KNO3) and CaCl2•6H2O + magnesium chloride hexahydrate (MgCl2•6H2O). For CaCl2•6H2O + KNO3, it was found that the melt temperature of the PCM could be varied by changing the percentage of KNO3. In the case of the CaCl2•6H2O + MgCl2•6H2O, phase diagram modeling and physical experiments were used to determine the correct eutectic mixture, which leads to congruent melting/freezing of this PCM. CaCl2•6H2O was also tested by DSC, with found Tm and Hf results similar to those presented in the literature. Finally, sodium sulfate decahydrate (Na2SO4•10H2O) and Na2SO4•10H2O + 25 wt% H2O were tested by DSC. For both of these PCMs, significant phase separation was observed, which must be addressed if these PCMs are to be used commercially.